Manifestaciones políticas desde la movilización y los espacios simbólicos de poder cultural - González Álvarez, Lázaro de Jesús; Rangel Giró, Masiel; Cuevas Arenas, Héctor; Estrada Casarín, Carlos E; Paz Díaz, Eduardo; Delgado Martínez, Edinson; Gómez Johnson, Cristina; Muñoz Balcázar, Kelly Giovanna; Meza Torres, Andrea; Valenzuela Moreno, Karla A; Guevara Hernández, Ilithya; Valenzuela Moreno, Karla A; et al. (Universidad Santiago de Cali, 2025)
Given the vast complexity of the study of the Social Sciences today, an inter-institutional group of researchers from different Latin American countries undertook the task of developing a joint project in which, each from their own lines of research, could present diverse political expressions. Whether from the perspective of political practices, social movements, displacement, or intercultural dialogue, the authors analyze diverse aspects of Latin American social reality, seeking to present new theoretical perspectives that allow us to shed light on phenomena that, until recently, had been little studied. The inter-institutional nature of the text has allowed the reader to observe very diverse views of a reality that, as previously mentioned, can be very complex.